The Origin of French Fries - Hess, Karen (Petits Propos Culinaires, 2001)
Here is a further instalment deriving from Karen Hess’ researches on the domestic manuscripts of Thomas Jefferson at Montecello, in this case investigating the popular notion that french fries should be included among the third US president’s gifts to posterity. It includes several historical recipes for fried potatoes as well as etymological evidence related to early references to potato.